Does the Eccentric Strength Profile of the Hamstrings Determine the Severity of Injury Sustained? - David Rhodes; Jill Alexander; Ryland Morgans; Mike Beere (International Journal of Sports Physical Therapy, 2025)
# Background and Purpose